The shapeshifters : the Kiesha'ra of the Den of Shadows - Atwater-Rhodes, Amelia (Kiesha'ra, 2010)
Collects five novels in which Danica Shardae, an avian shapeshifter, seeks peace between her people and the serpiente through a union with Zane Cobriana; a falcon named Nicias is sent to the homeland; Oliza Shardae Cobriana tries to keep the peace in Wyvern's Court; and Hai, a daughter of a falcon mother and cobra father, envisions destruction and tries to protect her home at all costs.